Surgical and Orthodontic Management of Fused Maxillary Central and Lateral Incisors in Early Mixed Dentition Stage - Suresh Ramamurthy; Ramaswamy Satish; Kalidass Priya (Hindawi Limited, 2014)
Fusion is one of the developmental dental anomalies in which two adjacent teeth are joined at the crown level forming a single tooth with an enlarged crown. Fusion causes some clinical problems such as unaesthetic appearance, pain, caries, and malocclusion. The management of fusion often needs multidisciplinary approach to give best possible esthetic and functional outcome. This paper reports a case of 9-year-old boy with fused maxillary left central and lateral incisors who was treated with 2×4 fixed orthodontic appliances after surgical separation of fused teeth.